Agrarian reform during the Rodríguez Lara administration - Guerrero Burgos, Rafael (Revolutionary nationalism: The 1970s and the Contemporary History of Ecuador, 2026)
It analyzes the reform as the cornerstone of the “nationalist and revolutionary” model aimed at modernizing the countryside and expanding the industrial market. Although 495,000 hectares were distributed and 57,000 families benefited, pressure from the production chambers prevented the elimination of large estates. The process preserved large estates, promoting extensive and inefficient livestock farming that monopolized public investment, leaving small producers in conditions of small-scale farming